Is Facial or Head Pain Related to the Location of Lesions on Computed Tomography in Chronic Rhinosinusitis?. (August 2017) - Yeo, Nam-Kyung; Park, Woo Joo; Ryu, In Sun; Lim, Hyun Woo; Song, Yong Jin
Background: Facial or head pain is not an infrequent symptom among patients diagnosed with chronic rhinosinusitis (CRS), but few reports have investigated the pain in CRS, including the relationship between pain and sites of CRS. The aim of this study was to investigate whether pain is related to the location of lesions on computed tomography (CT) in CRS. Methods: We analyzed 203 patients who underwent endoscopic sinus surgery (ESS) for 2 years. Patients were assessed using the questionnaires on pain, provided 1 day prior to the operation and 6 months post operation. Sites of CRS were evaluated using CT. We analyzed whether the degree of inflammation in each sinus had an effect on the location of pain. Results: Seventy-eight patients (38.4%) had preoperative facial or head pain. There was no difference in the sinus inflammation scores in CT findings, based on the presence of pain. Pain was most commonly located in the periorbital area, followed by the frontal, vertex, occipital, and facial areas. No significant correlation was found between the sinuses and the location of pain. Conclusions: This study indicates that in CRS patients, several sites of pain are involved, particularly in the periorbital area; these sites were not found to be related to the location of CRS.